SIMULATOR MINI SCADA SEBAGAI PEDOMAN DASAR PENANGANAN GANGGUAN FUNGSI KONTROL SISTEM SCADA PADA PMT 20 KV DI PT PLN (PERSERO) APD JATENG DAN DIY - , MEI PRIYANTO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
PT. PLN (Persero) has implemented a variety of ways to improve the reliability and efficiency of the distribution electrical power to arrive at the consumer, one of them was already made SCADA system. SCADA (Supervisory Control and Data Acquisition) is a system that serves as a means of long-distance supervision and monitoring. SCADA consists of the Master, Workstation and RTU (Remote Terminal Unit). Master is a device that serves as a database sistem to be monitored while control is done through Workstation (HMI). RTU is a device used as telecontroling, telesignaling and telemetering. The system communicates using a communication network such as Fiber Optic, radio etc. SCADA in PT PLN (Persero) APD Central Java and DIY use on 20 KV PMT. In the existing SCADA system there are often problems of communication. That fail the telecontrol, telesignaling, and telemetering functions of workstations (HMI). This means that the SCADA system is not functioning optimally or SCADA Performance of became decreased. The duration of handling disruption in SCADA communications failed. One cause that is caused due to the limited knowledge engineer of the wiring sistem SCADA (both RTU, Master (HMI) or Telecommunications) or PMT wiring terminal for SCADA remote control and also due to the difficulty engineers can find the cause of the failure function remote control. The authors consider the importance of practical modules SCADA or SCADA Mini Simulator that can be used as a medium of learning practical and basic guidelines in handling disruption troubleshooting analysis control function. The Simulator consists of RTU Simulator, HMI Simulator and PMT Simulator. So that, it is expected by the Simulator are indirectly able to increase the performance of SCADA.